Design and synthesis of novel 2, 4-diaryl-5H-indeno[1, 2-b]pyridine derivatives, and their evaluation of topoisomerase inhibitory activity and cytotoxicity. Issue 1 (1st January 2015) - Kadayat, Tara Man; Park, Chanmi; Jun, Kyu-Yeon; Magar, Til Bahadur Thapa; Bist, Ganesh; Yoo, Han Young; Kwon, Youngjoo; Lee, Eung-Seok
Graphical abstract: Abstract: For the development of potential anticancer agents, we designed and synthesized 30 new 2, 4-diaryl-5 H -indeno[1, 2- b ]pyridine derivatives containing aryl moiety such as furyl, thienyl, pyridyl, and phenyl at 2- and 4-position of 5 H -indeno[1, 2- b ]pyridine. They were evaluated for topoisomerase I and II inhibitory activity, and cytotoxicity against several human cancer cell lines. Among prepared 30 compounds, 7, 8, 9, 10, 12, 14, 16, 19, 20, 22, and23 with 2- or 3-furyl and/or 2- or 3-thienyl either at 2- or 4-position of central pyridine showed the significant or moderate topoisomerase II inhibitory activity. Compounds7, 8, 11, 12, 13, and22 with 2-furyl, 2-thienyl or 3-thienyl at 2-position of central pyridine showed the significant or moderate topoisomerase I inhibitory activity. Especially, compound12 with strong topoisomerase II inhibitory activity at 100 μM and 20 μM, and moderate topoisomerase I inhibitory activity displayed strong cytotoxicity against several human cancer cell lines.